2010
DOI: 10.1155/2010/976901
|View full text |Cite
|
Sign up to set email alerts
|

New Thermal and Microbial ResistantMetal‐ContainingEpoxy Polymers

Abstract: A series of metal-containing epoxy polymers have been synthesized by the condensation of epichlorohydrin (1-chloro-2,3-epoxy propane) with Schiff base metal complexes in alkaline medium. Schiff base was initially prepared by the reaction of 2,6 dihydroxy 1-napthaldehyde and o-phenylenediamine in 1  :  2 molar ratio and then with metal acetate. All the synthesized compounds were characterized by elemental, spectral, and thermal analysis. The physicochemical properties, viz., epoxy value, hydroxyl content, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 24 publications
3
2
0
Order By: Relevance
“…The FTIR spectrum of the PS‐Ni complex (Figure 1) showed the absorption peak of the C═N band had shifted compared with the analogous band in the spectrum of the PS‐ligand, which indicated the coordination between the imine nitrogen atoms and the central metal ions. [ 25 ] The NH 2 bands in the region 1350–1370 cm −1 observed in the spectrum of the PS‐ligand were weakened in that of the PS‐Ni complex, which agreed well with the results of element analysis.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The FTIR spectrum of the PS‐Ni complex (Figure 1) showed the absorption peak of the C═N band had shifted compared with the analogous band in the spectrum of the PS‐ligand, which indicated the coordination between the imine nitrogen atoms and the central metal ions. [ 25 ] The NH 2 bands in the region 1350–1370 cm −1 observed in the spectrum of the PS‐ligand were weakened in that of the PS‐Ni complex, which agreed well with the results of element analysis.…”
Section: Resultssupporting
confidence: 87%
“…[ 38 ] Then, ethylene continued to coordinate to (C) and insert to CH bond to form intermediates (D), (E), or (G) simultaneously. When the reaction process followed the reaction path (A)—(B)—(C)—(D)/(E)—(F), an increasing confinement effect of the ligand led to an increase of β‐H elimination thus to light olefin, [ 25 ] and the large steric hindrance of the long polymer chains at PS‐ligand influenced the availability of the axial coordination sites of the catalytic center, which also promoted the β‐H elimination reaction then produced more C 4 –C 6 olefins (Table 2). Therefore, the poly Schiff‐base ligand acted as a steric hindrance for the formation of less internal olefins.…”
Section: Resultsmentioning
confidence: 99%
“…It could be concluded that the main functional groups in PS‐800‐90 were hydroxyl, carboxyl, aryl ether, and CH on the aromatic carbon skeleton. Compared with the fresh adsorbent, the red shift of –OH to 3,437 cm −1 in the spent adsorbent suggested the presence of intermolecular hydrogen bonding between the carbonyl group (CO) on the surface of PS‐800‐90 and the phenolic hydroxyl group (–OH) of phenol . A more significant peak at 1,436 cm −1 (CC vibrations in aromatic rings) revealed the adherence of phenol on the surface of PS‐800‐90, which was also confirmed by the SEM‐EDS results of the fresh and spent PS‐800‐90 shown in Figure S5.…”
Section: Resultssupporting
confidence: 63%
“…Compared with the fresh adsorbent, the red shift of -OH to 3,437 cm −1 in the spent adsorbent suggested the presence of intermolecular hydrogen bonding between the carbonyl group (C¼O) on the surface of PS-800-90 and the phenolic hydroxyl group (-OH) of phenol. 47 A more significant peak at 1,436 cm −1 (C¼C vibrations in aromatic rings) revealed the adherence of phenol on the surface of PS-800-90, which was also confirmed by the SEM-EDS results of the fresh and spent PS-800-90 shown in Figure S5. A smoother surface with less pores and cracks on the SEM micrograph and higher weight percentage of C element from the results of EDS were observed in PS-800-90 due to the adsorption of phenol.…”
Section: Adsorption Mechanismsupporting
confidence: 60%
“…A broad band at 3420 cm À1 was due to the vibrations of the free hydroxyl group of alcohol [32]. The decrease in the broadening of the peak in this region was due to the presence of intermolecular hydrogen bonding, which is possible between the hydrogen of the hydroxyl group and the oxygen of the carbonyl group [33,34]. The peak at 1420 cm À1 was assigned to O-H inplane bending vibration.…”
Section: Characterizationmentioning
confidence: 99%